2010
DOI: 10.1258/ht.2010.010015
|View full text |Cite
|
Sign up to set email alerts
|

The Southampton Dupuytren's Clinic: audit of an effective multidisciplinary model

Abstract: Introduction. The Southampton Dupuytren's Clinic (SDC) was preceded by a four-month period when the therapist accompanied the surgeon in Clinic to learn about Dupuytren's Disease (DD) and to develop a specific proforma to collect details of the patient, the condition and the planned treatment. Methods. A special clinic was set up for general practitioner referrals for patients with DD. Each patient was seen by the therapist. A detailed history and examination were recorded on the proforma. Treatment options to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Emerging evidence suggests that allied health professionals working in primary contact roles can be costeffective, reduce waiting times and waiting lists, and improve patient flow and patient satisfaction while maintaining the quality and safety of services (Burn & Beeson, 2014;Dawson & Ghazi, 2004;Oldmeadow et al, 2007;Saxon, Gray & Oprescu, 2014;Warwick, Belward, Vadher & Setty, 2010). O'Brien, Hardman and Goldby (2013) found that a statistically significant predictor for not requiring surgery was when patients received nonoperative treatment by an occupational therapist.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence suggests that allied health professionals working in primary contact roles can be costeffective, reduce waiting times and waiting lists, and improve patient flow and patient satisfaction while maintaining the quality and safety of services (Burn & Beeson, 2014;Dawson & Ghazi, 2004;Oldmeadow et al, 2007;Saxon, Gray & Oprescu, 2014;Warwick, Belward, Vadher & Setty, 2010). O'Brien, Hardman and Goldby (2013) found that a statistically significant predictor for not requiring surgery was when patients received nonoperative treatment by an occupational therapist.…”
Section: Introductionmentioning
confidence: 99%
“…Given that Dupuytren's disease is progressive, and recurrence is common after intervention, it is essential that a deeper understanding of the patient journey over time is developed so that patients can be supported to make informed decisions regarding their treatment options. The growing role of occupational therapists in primary contact positions, where they perform extended scope screening and treatment planning roles (Warwick et al, 2010;Cox et al, 2020;Glasgow et al, 2020), means that this knowledge is important for the profession. Further longitudinal research would be beneficial to explore this aspect, as well as to gain a deeper understanding of the ways in which individuals adapt to the condition.…”
Section: Reviewmentioning
confidence: 99%